2017
DOI: 10.11604/pamj.2017.28.246.9606
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum assisted closure technique: a short review

Abstract: The management of difficult to heal wounds has always been a cause of concern for the treating clinicians. There has been a tremendous increase in the number patients presenting with difficult to heal wounds. The conventional techniques have been in use since the long time for the management of these wounds, yet desired results are not achieved always. Thus a newer novel technique which might be useful in the difficult to heal wounds and delivering at par or better results as compared to the conventional techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(23 citation statements)
references
References 34 publications
0
18
0
1
Order By: Relevance
“…Negative pressure wound therapy is used more and more in the last two decades for wound healing. The principal indications for using NPWT are acute and traumatic lesions, dehisced incisions, stasis, diabetic or pressure ulcers, flaps and meshed grafts [7]. In NF application of NPWT is a vital step after the removal of the septic fascia together with the unhealthy tissue [8].…”
Section: Resultsmentioning
confidence: 99%
“…Negative pressure wound therapy is used more and more in the last two decades for wound healing. The principal indications for using NPWT are acute and traumatic lesions, dehisced incisions, stasis, diabetic or pressure ulcers, flaps and meshed grafts [7]. In NF application of NPWT is a vital step after the removal of the septic fascia together with the unhealthy tissue [8].…”
Section: Resultsmentioning
confidence: 99%
“…Yadav et al have found better results with NPWT in managing chronically infected wounds compared with conventional technique [12]. Cozza et al conducted a prospective experimental study including more than 10 patients and found that NPWT is not a risk factor for health care personnel associated with the management of infections [13].…”
Section: Discussionmentioning
confidence: 99%
“…The sizes of soft tissue defects, reduced from 69.18 cm 2 to 50.73 cm 2 after VAC in their study. Yadav S et al proposed that this novel VAC technique helps in the management of difficult wounds [8]. It has always been a cause of concern for the treating clinicians and VAC delivers at par or better results as compared to the conventional techniques.…”
Section: Discussionmentioning
confidence: 99%